Analisis Dampak Kebijakan Kenaikan Tarif Pajak Pertambahan Nilai (PPN) Menggunakan Pendekatan Inkremental - Putri Aulia Ramadhani; Wulan Desliana; Umima; Ipah Ema Jumiati (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
This study uses an incremental approach to thoroughly analyze the policy of increasing the Value Added Tax (VAT) rate from 10% to 11%. The study also analyzes the implications and impacts of this policy on various sectors. The incremental approach emphasizes gradual and sustainable policy adjustments, focusing on practical improvements while considering community needs and resource constraints. The VAT increase is included in the Tax Harmonization Law (UU HPP) to strengthen Indonesia's fiscal capacity and significantly address the budget deficit caused by the COVID-19 pandemic. The methods used in this study are a literature review and various previous studies relevant to the focus of this study. The findings show that although this policy aims to stabilize state revenue and support national recovery programs, it also poses challenges for the community and business actors. On the negative side, the VAT increase has led to higher costs for goods and services, thereby reducing household purchasing power, especially for low- and middle-income groups. Additionally, small and medium-sized enterprises (SMEs) are facing increased production costs, which impact profits and competitiveness. This study highlights the dual impact of the VAT increase, balancing its role in fiscal recovery with the socio-economic challenges it creates.